Line-of-sight quantum key distribution with differential phase shift keying - Hiroyuki Endo; Toshihiko Sasaki; Masahiro Takeoka; Mikio Fujiwara; Masato Koashi; Masahide Sasaki (New Journal of Physics, 2022)
Free-space optical (FSO) links offer a practical approach to realize quantum key distribution (QKD) in a global scale. However, when one wants to further extend the distance from the geostationary orbit to the ground, currently known QKD schemes cannot realize practical key rates mainly due to the diffraction losses of a laser beam. If the facts that the FSO links are highly directional and must be used in the line-of-sight (LoS) condition are taken into account, one may impose some physical restrictions on an eavesdropping model to explore longer-distance QKD. In this paper, we propose a novel FSO secret key agreement scheme, line-of-sight QKD (LoS-QKD), based on a quantum wiretap channel. In our model, an eavesdropper can tap only a limited fraction of the FSO signal beam but perform any physically allowable operations on the tapped signals. Fading effects which are significant in the FSO links are fully taken into account. We provide a security proof for the differential phase shift (DPS) keying scheme in terms of the metric which meets the composability. We investigate numerically the performances of LoS-QKD with DPS keying, including finite-length analysis, showing that our proposed scheme can realize high-speed and long-distance secret key agreement with information-theoretic security.